How Bangladesh can gain from managing floodwater - Bhaduri, Tanmoy; Alam, Mohammad Faiz (International Water Management Institute, 2025)
Floodwater management offers a promising opportunity for Bangladesh’s agriculture to tackle water scarcity, mitigate flooding and promote sustainable development.